MRT letter: Nanoscopy of protein colocalization in living cells by STED and GSDIM - Lalkens, Birka; Hell, Stefan (Microscopy research and technique, 2012)
We report the use of superresolution fluorescence microscopy for studying the nanoscale distribution of protein colocalization in living mammalian cells. Nanoscale imaging is attained both by a targeted and a stochastic fluorescence on-off switching superresolution method, namely by stimulated emission depletion (STED) and ground state depletion microscopy followed by individual molecular return (GSDIM), respectively. Analysis of protein colocalization is performed by bimolecular fluorescence complementation (BiFC). Specifically, a nonfluorescent fragment of the yellow fluorescent protein Citrine is fused to tubulin while a counterpart nonfluorescent fragment is fused to the microtubulin-associated protein MAP2 such that fluorescence is reconstituted on contact of the fragment-carrying proteins. Images with resolution down to 65 nm prove a powerful new way for studying protein colocalization in living cells at the nanoscale. Microsc. Res. Tech., 2012. © 2011 Wiley Periodicals, Inc.
Published online 15 June 2011
Gesehen am 31.10.2018